Highly permeable acid-resistant polyamine hollow fiber nanofiltration membrane fabricated by secondary interfacial polymerization reactions - Yin, Yurong (2025)
The development of acid-resistant nanofiltration (NF) membranes has drawn much attention due to their application in industrial wastewater treatment. In this work, we utilized polyethyleneimine (PEI) and cyanuric chloride (CC) to conduct the first interfacial polymerization (IP) reaction on the polyethersulfone (PES) hollow fiber substrate, followed by the secondary IP process using tris(2-aminoethyl) amine (TAEA) to react with the residual chloride groups after the first IP to improve the positive charge intensity of the membrane surface. Compared to the pristine membrane formed after the first IP, the TAEA-optimized membrane exhibited a high pure water permeability (PWP) of 25.2 L m−2 h−1 bar−1 and nearly 90 % rejection to MgCl2 at 2 bar operating pressure. Meanwhile, when treating synthetic electroplating rinse water, the membrane was still able to achieve 85 % rejections to Cu2+ and Ni2+ ions during a 7-day operation test under pH of 1 condition. The results demonstrate the good potential of the membrane for heavy metal ions removal in industrial acidic wastewater.